Precipitation Gradient and Maximum 24-Hour Rainfall in the Chahardangeh Watershed - Mojtaba Farhadzadeh; Fatemeh Tamjid; Parisa Maleki (مهندسی و مدیریت ساخت, 2025)
Spatial variations in precipitation have diverse effects on water resource management at the watershed level. Therefore, analyzing the spatial distribution of various precipitation parameters is crucial for estimating water balance errors and improving decision-making processes. This study aims to investigate the distribution of monthly and seasonal precipitation, precipitation gradient, estimation of maximum 24-hour rainfall, and the development of an annual isohyetal map for the Chahardangeh watershed in Sari, Mazandaran Province. To analyze annual precipitation in the study area, data from 23 meteorological stations, selected based on quantitative and qualitative adequacy, were used for a 50-year reference period (1972–2022). The isohyetal map was generated in a GIS environment using data from all stations within the reference period and auxiliary stations for validation purposes. The results indicate that autumn and winter account for over 60% of the total seasonal precipitation in the Chahardangeh watershed. The precipitation gradient curve reveals a negative correlation between elevation and precipitation, meaning that rainfall decreases as elevation increases. Based on the isohyetal map, the average annual precipitation in the Chahardangeh watershed is approximately 479 mm. The maximum 24-hour rainfall for 2-year and 100-year return periods was estimated using an averaging method, yielding approximately 44 mm and 103 mm, respectively.